The doctrine of resurrection and immortality and its impact on the construction of Egyptian civilization - Khalil, Mariam Nasser Hassen Ibrahim (Journal of Humanities & Social Sciences, 2022)
This research has followed the descriptive and analytical approach in studying the perception of the doctrine of the Baath and immortality in the ancient Egyptians, and the historical approach in drawing on the evidence that proves the importance of that doctrine, whose effects still exist to this day, one of the most important findings of the research is that the belief in a religious idea old so what This belief was an incentive that excites the same Egyptian man to reach him, so he built a whole civilization for him that included the Great Pyramids that were counted as tombs of Kings to preserve their bodies, and the invention of taxidermy science, and he built huge temples, which included the inscriptions of the lives of the dead desired in the other world, that is, all.